Edukasi Penggunaan Aplikasi Zoom Untuk Menunjang Pemberdayaan Diri Perempuan Paruh Baya - Sulidar Fitri; Hani Rubiani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The Women Entrepreneurs Community is one of the groups of women who become lumberjacks in the Special Region of Yogyakarta. Some are housewives and some are working mothers. Since the 2020 pandemic, many activities have to be done almost entirely online from home. In relation to these situations, women also need to keep up with developments in information technology in order to be able to keep up with the latest developments in the current situation. All these mothers, especially those over the age of 40, have a good knowledge of existing programs on mobile phones and laptops, especially the Zoom application, and are able to attend widely available seminars and online training courses. It does not mean—self quality. The recovery to the new normal is still underway, but so far there are many online activities that require the use of the Zoom application. It is essential to know more about the use of information technology, such as the use of the Zoom application at home. As a result of this activity, mothers in the community are becoming more knowledgeable about information technology in their self-development activities.